2021
DOI: 10.3389/fmicb.2021.583834
|View full text |Cite
|
Sign up to set email alerts
|

PF-429242, a Subtilisin Inhibitor, Is Effective in vitro Against Leishmania infantum

Abstract: PF-429242 is an inhibitor of subtilisin, an important protease found in Leishmania. However, studies regarding the effect of PF-429242 on Leishmania are scarce. In this work we evaluated the antileishmanial effect of PF-429242 against Leishmania infantum and the mechanism involved in the death of the parasite. PF-429242 had low toxicity against mammalian cells (peritoneal macrophages) (CC50 = 189.07 μM) and presented activity against L. infantum promastigotes (IC50 = 2.78 μM) and intracellular amastigotes (IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…TPCK has already been shown to reduce serine protease activity of L. amazonensis [ 34 ]. Interestingly, PF-429242, a serine protease inhibitor previously studied by our group, was active against both L. infantum promastigotes (IC 50 = 2.78 μM) and amastigotes (IC 50 = 14.07 μM), displaying parasite selectivity over the host cell [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPCK has already been shown to reduce serine protease activity of L. amazonensis [ 34 ]. Interestingly, PF-429242, a serine protease inhibitor previously studied by our group, was active against both L. infantum promastigotes (IC 50 = 2.78 μM) and amastigotes (IC 50 = 14.07 μM), displaying parasite selectivity over the host cell [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, TPCK showed low toxicity in mammalian cells and was found to be selective for the parasite when compared to host cells. Interestingly, our research group has previously demonstrated that PF-429242 also exhibits low toxicity against peritoneal macrophages [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 The increased level of ROS was observed in L. infantum promastigotes after treatment with PF-429242 (a subtilisin inhibitor) in contrast to untreated control parasites. 49 Also, caffeic acid induces high ROS generation through oxidative burst, which leads to the death of Leishmania amazonensis promastigotes. 50 The health of any cell depends on its intact boundary or cellular membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescent nanoparticles have a 700–750 nm excitation wavelength and an emission of 750–800 nm. In this experiment, rhodamine 123 and Nile Red were used as our fluorescent markers in this experiment (Machado et al., 2021 ). The Nile Red is lipophilic and insoluble in water, mimicking nanoparticles' characteristics.…”
Section: Characterization Of Cationic Nanoparticlesmentioning
confidence: 99%